Usefulness of 2‐D shear wave elastography for the diagnosis of inguinal lymph node metastasis of malignant melanoma and squamous cell carcinoma. Issue 11 (13th August 2020) - Kawahara, Yu; Togawa, Yaei; Yamamoto, Yosuke; Wakabayashi, Seiichiro; Matsue, Hiroyuki; Inafuku, Kazuhiro
Abstract: We used 2‐D shear wave elastography to quantify lymph node hardness, from the shear wave velocity, to determine the presence or absence of metastatic lymphadenopathy in the inguinal lymph nodes of five patients with malignant melanoma and squamous cell carcinoma. The shear wave velocity accurately identified all cases of metastasis confirmed by histology, compared with two false‐positive and one false‐negative finding with positron emission tomography/computed tomography. 2‐D shear wave elastography would be useful to evaluate inguinal lymph node metastasis.